Answer: i think its c 1,0763
Step-by-step explanation:
rhoumbus that is what I use and got right!!
Step-by-step explanation:
The coordinate of the point is (6,-2)
<h3>How to determine the coordinate of the point?</h3>
The given parameters are:
A = (1,8)
B = (7,-4)
The location of the point (i.e 5/6) means that the ratio is:
m :n = 5 : (6 - 5)
m : n = 5 : 1
The coordinate of the point is then calculated as:
![(x,y) = \frac{1}{m + n}* (mx_2 + nx_1,my_2 + ny_1)](https://tex.z-dn.net/?f=%28x%2Cy%29%20%3D%20%5Cfrac%7B1%7D%7Bm%20%2B%20n%7D%2A%20%28mx_2%20%2B%20nx_1%2Cmy_2%20%2B%20ny_1%29)
So, we have:
![(x,y) = \frac{1}{5 + 1}* (5 * 7 + 1 * 1 , 5 * -4 + 1 * 8)](https://tex.z-dn.net/?f=%28x%2Cy%29%20%3D%20%5Cfrac%7B1%7D%7B5%20%2B%201%7D%2A%20%285%20%2A%207%20%2B%201%20%2A%201%20%2C%205%20%2A%20-4%20%2B%201%20%2A%208%29)
Evaluate
![(x,y) = \frac{1}{6}* (36 , -12)](https://tex.z-dn.net/?f=%28x%2Cy%29%20%3D%20%5Cfrac%7B1%7D%7B6%7D%2A%20%2836%20%2C%20-12%29)
Evaluate the product
(x,y) = (6,-2)
Hence, the coordinate of the point is (6,-2)
Read more abut line segment ratio at:
brainly.com/question/12959377
#SPJ1
Answer:
Step-by-step explanation:
The point slope form of a straight line is expressed as
y - y1 = m(x - x1)
Where
m represents slope of the line
y1 represents the initial value of y
x1 represents the initial value of x
If two lines are parallel, it means that they have the same slope. From the equation of the given line, slope = 1/2
Therefore,
m = 1/2
x1 = - 3
y1 = - 2
Substituting into the point slope equation, it becomes
y - - 2 = 1/2(x - - 3)
y + 2 = 1/2(x + 3)
The equation is
y + 2 = 1/2(x + 3)
Answer:
1:
×![2](https://tex.z-dn.net/?f=2)
2: ![y^6](https://tex.z-dn.net/?f=y%5E6)
Step-by-step explanation:
1:
Multiply the numbers: ![y(^3^*^2)](https://tex.z-dn.net/?f=y%28%5E3%5E%2A%5E2%29)
![3*2 = 6](https://tex.z-dn.net/?f=3%2A2%20%3D%206)
Write it without exponents:
so
.
2:
![(y^3)^2](https://tex.z-dn.net/?f=%28y%5E3%29%5E2)
Apply exponent rule :
assuming ![a\geq 0](https://tex.z-dn.net/?f=a%5Cgeq%200)
![(y^3)^2=y^3^*^2](https://tex.z-dn.net/?f=%28y%5E3%29%5E2%3Dy%5E3%5E%2A%5E2)
![=y^3^*^2](https://tex.z-dn.net/?f=%3Dy%5E3%5E%2A%5E2)
Multiply the numbers: ![3 * 2 = 6](https://tex.z-dn.net/?f=3%20%2A%202%20%3D%206)
![= y^6](https://tex.z-dn.net/?f=%3D%20y%5E6)
Hope I helped! If so, may I get Brainliest and a Thanks?
Thank you, have a good one! =)